The Effects of Using Waste Engine Oil Bottom on Physical, Rheological Properties and Composite Modification Mechanism of SBS-Modified Asphalt - Yanbo Wang; Ailian Liu; Weixiang Ding; Fangping Rao; Jun Yuan; Zhihua Zhang; Zhen Xu; Chuanzhou Dong (Advances in Materials Science and Engineering)
This research explores the effects of using waste engine oil bottom on physical, rheological properties and composite modification mechanism of SBS-modified asphalt. The SBS asphalt binder was modified by WEOB with different concentrations (2, 4, and 6 wt%). The GC-MS and FTIR spectrometry were conducted to evaluate the chemical compositions of WEOB- and WEOB-modified asphalt. RV, DSR, and BBR were tested to evaluate high- and low-temperature pavement performance. Fluorescence microscope (FM) test, bar thin layer chromatograph (BTLC) test, and AFM test were performed to evaluate the micromorphologies and modification mechanism. The test results showed that a new characteristic peak appeared in the infrared spectrum of the WEOB-modified SBS asphalt, indicating a chemical reaction in the modification process. Incorporation of WEOB improves both the high-temperature and low-temperature properties of the SBS asphalt binder. It was confirmed that with the increase of WEOB concentration, the content of colloid gradually increases, which promotes the swelling and compaction of SBS polymer network structure. Furthermore, WEOB promotes the polarity of SBS and forms graft product MAH-g-SBS with asphalt, thus inhibiting the thermal movement of asphalt molecules. On the contrary, light components have a good correlation with the surface roughness of modified asphalt; the results show that the modified asphalt has good rutting resistance.